Intravenous Lipid Emulsion Therapy in Drug Overdose and Poisoning: An Updated Review - Sevdegül Bilvanisi; Müge Gülen; Mustafa Sabak; Şeniz Demiryürek; Abdullah Tuncay Demiryürek (Eurasian Journal of Medicine)
The use of intravenous lipid emulsion (ILE) is thought to reverse the acute neurological and cardiac toxicities generated by local anesthetic and non-anesthetic drugs. The aim of this review is to provide an updated overview of ILE therapy in the management of the toxic efects of medications on humans. Indications, mechanisms of action, monitoring, dosing, lipid formulations, adverse efects, and contraindications related to ILE are highlighted. Although ILE therapy was initially utilized for local anesthetic toxicity, its use has been extended to patients with overdoses or poisoning induced by various non-local anesthetic drugs. It has been proposed that intravenous lipid droplets generate a discrete lipophilic phase in the bloodstream into which liposoluble drugs preferentially partition. This partitioning efect, known as the lipid sink phenomenon, is thought to decrease the quantity of drug content in tissues in vital organs. At the same time, other studies have also described several molecular mechanisms that may contribute to ILE efcacy. Potential adverse efects of ILE have also been identified, such as pulmonary toxicity, hypertriglyceridemia, acute pancreatitis, interference with laboratory measurements, fat overload syndrome, worsening of systemic absorption of toxin, and hepatic dysfunction. Intravenous lipid emulsion therapy is gaining wider acceptance in critical care units and emergency rooms as a possible treatment modality for liposoluble drug toxicity. Currently, recommendations on ILE administration in clinical toxicology are mainly based on published case reports and animal studies. Thus, further clinical studies are required to increase knowledge about ILE therapy.